(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
This paper aims to address the issue of the fundamental rights of imprisoned women. The first analysis focuses on researching the profile of this layer of the population, known to few, and above all its numerical representation in society and its main common characteristics. With this data, we will move on to study the fundamental rights applicable to these women and granted to them in particular by the Brazilian Constitution. We will go through the principles of human dignity and humanity, giving a general aspect to the category of prisoners, since they are more comprehensive. Next, the analysis of the topic requires consideration of public policies, since, according to our research, norms, doctrine and the National Meeting on Women’s Imprisonment, promoted by the National Council of Justice in June 2011, conclude and call for public policies that ensure compliance with the fundamental rights of incarcerated women.